2016
DOI: 10.1021/acs.est.6b03434
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Interaction of Eu3+with Microbiologically Induced Calcium Carbonate Precipitates using TRLFS

Abstract: The microbial induced biomineralization of calcium carbonate using the ureolytic bacterium Sporosarcina pasteurii in the presence of trivalent europium, a substitute for trivalent actinides, was investigated by time-resolved laser-induced fluorescence spectroscopy (TRLFS) and a variety of physicochemical techniques. Results showed that the bacterial-driven hydrolysis of urea provides favorable conditions for CaCO precipitation and Eu uptake due to subsequent increases in NH and pH in the local environment. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 51 publications
0
1
0
1
Order By: Relevance
“…10 One important process affected by GlcA coordination is biomineralization, where EPS are presumed to be involved in metal transport processes. 7 Prior experiments in our group have shown that trivalent lanthanides (Ln), namely Eu(III), can be incorporated into minerals formed through a biologically induced mechanism, 11 and it appears reasonable to assume the same process would prevail with An(III). 12,13 A substitution of An(III) for Ca 2+ in a biomineralization process is also the proposed mechanism for its incorporation into bone, which is mainly responsible for the long biological halflife of these elements.…”
Section: Introductionmentioning
confidence: 99%
“…10 One important process affected by GlcA coordination is biomineralization, where EPS are presumed to be involved in metal transport processes. 7 Prior experiments in our group have shown that trivalent lanthanides (Ln), namely Eu(III), can be incorporated into minerals formed through a biologically induced mechanism, 11 and it appears reasonable to assume the same process would prevail with An(III). 12,13 A substitution of An(III) for Ca 2+ in a biomineralization process is also the proposed mechanism for its incorporation into bone, which is mainly responsible for the long biological halflife of these elements.…”
Section: Introductionmentioning
confidence: 99%
“…Key words: Na-Ti 3 C 2 T x ; Eu(III); removal; interaction mechanism 近年来随着核能利用的快速发展, 由反应堆核 燃料燃烧生成的乏燃料总量不断增加, 其后处理过 程也伴随着大量放射性废物的产生。以 241 Am、 243 Am 和 244 Cm 为代表的三价次锕系核素以及部分 镧系裂变产物(如 155 Eu)均具有强放射毒性和长半衰 期寿命 [1][2] , 如处置不当将对生态环境和人类健康 造成严重威胁。例如, 241 Am 的过量暴露可引发骨髓 受损等急性放射病, 还会显著增加患各类慢性炎症 (肝炎、肾炎)以及癌症等疾病的风险 [3] 。因此如何能 够高效快速地去除这些关键放射性核素已成为备受 关注的重要环境议题 [4][5][6][7] 。由于具有非常相近的物理 化学性质以及环境迁移行为, Eu(III)通常作为三价 次锕系元素以及其他镧系元素的化学模拟物, 被用 来开展相应的宏观吸附行为和光谱学性质研究。在 过去几十年中 Eu(III)与氧化铝 [8][9][10] 、TiO 2 [11][12] 、粘 土矿物 [13][14][15] 和碳基材料 [16][17][18][19] 之间的相互作用得到了 广泛的研究。人们重点考察了 pH、离子强度、腐殖 质等环境因素对固体颗粒吸附 Eu(III)的影响。然而, 较慢的吸附动力学以及较低的吸附容量等诸多缺点 限制了这些材料在环境水体中清除次锕系与镧系放 射性核素的实际效果。 二维过渡金属碳/氮化物(MXene)是 2011 年后 发现的一族新型层状纳米材料, 因其具有优越的物 理化学性质而受到人们的关注, 已在能量储存 [20][21][22][23][24] , 高 效 催 化 [25][26][27] , 电 磁 吸 收 和 屏 蔽 [28][29][30] 和 化 学 传 感 [31][32][33] 等方面被广泛应用。 由于 MXene 具有良好的 亲水性、负的表面电荷、优异的离子插层能力以及 大量的活性吸附位点 [34][35][36] 。其在水处理和环境修复 领域也崭露头角(已有文献报导 MXene 可对染料分 子、重金属离子和放射性核素进行有效去除) [37][38][39][40][41][42][43] 具有典型的层状堆叠结构, 这与之前的文献报道一 致...…”
unclassified